1989
DOI: 10.1002/ar.1092230203
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 35S‐Sulfate within the transseptal ligment of the mouse

Abstract: The distribution of 35S-sulfate-labeled macromolecules was examined within three regions of the transseptal ligament: the 1) mesial, 2) middle and 3) distal thirds. Swiss mice, 6 weeks of age, were injected with 35S-sulfate and killed after 1, 6, and 12 hours and 1, 2, 3, 4, 5, and 7 days. Silver grains and cell nuclei were counted on autoradiographs which had been counterstained by the Van Gieson method, and mean counts were analyzed statistically. Analysis of variance revealed no significant differences in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(35 reference statements)
0
2
1
Order By: Relevance
“…Half-lives for the turnover of labeled glycoproteins in 6-wk mice (middle third, 5.8 d; mesial third, 5.6 d; distal third, 5.7 d) was different than that calculated by this laboratory for 6-wk animals injected with '•'^S-sulfate (middle third, 3.5 d; mesial and distal thirds, 3.6 d) (Johnson 1986) and ^H-proline (middle third, 16.9 d; mesial third, 18.3 d; distal third. 18.5 d) (Johnson, unpublished observation), suggesting that glycoprotein turnover in the transseptal ligament might occur more slowly than that of sulfated glycosaminogiycans but more rapidly that collagen.…”
Section: Discussioncontrasting
confidence: 62%
“…Half-lives for the turnover of labeled glycoproteins in 6-wk mice (middle third, 5.8 d; mesial third, 5.6 d; distal third, 5.7 d) was different than that calculated by this laboratory for 6-wk animals injected with '•'^S-sulfate (middle third, 3.5 d; mesial and distal thirds, 3.6 d) (Johnson 1986) and ^H-proline (middle third, 16.9 d; mesial third, 18.3 d; distal third. 18.5 d) (Johnson, unpublished observation), suggesting that glycoprotein turnover in the transseptal ligament might occur more slowly than that of sulfated glycosaminogiycans but more rapidly that collagen.…”
Section: Discussioncontrasting
confidence: 62%
“…It is well known that both the PDL and the alveolar wall have regional variations in collagenous protein metabolism (Diaz, 1978;Beertsen, 1979;Vignery and Baron, 1980;Johnson, 1986;Nemeth et al, 1989). However, previous studies have not quantified the regional variations in sGAG concentrations within either the PDL or the adjacent alveolar wall (Baumhammers and Stallard, 1968;Bartold, 1987;Kirkham et al, 1992;Okazaki et al, 1992;Kagayama et al, 1996;Evefls et al, 1998), even though regional variations in their concentrations have been reported within the transseptal ligament (Johnson, 1989). Our study extends previous studies by reporting regional variability in the comparative sGAG and collagenous protein metabolism within both the PDL and the adjacent alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…There are qualitative (Baumhammers and Stallard,1968; Lau et al,1983) but no quantitative studies of regional variations in the metabolism of 35 S‐sulfate (which is a marker for sGAG metabolism) within the PDL during physiologic tooth movements, although these data are available for the PDL collagenous proteins (Rippin,1976; Diaz,1978; Johnson,1986, 2005). A previous study reported significant regional variations in 35 S‐sulfate metabolism within the transseptal ligament of the mouse during physiologic drift of the molar teeth (Johnson,1989), and we hypothesized that regional variations in the distribution and metabolism of sGAG would also be evident within the PDL of the rat molar dentition. The objective of the present study was to compare the collagenous protein and sGAG metabolism at three levels of the PDL (cervical, middle, and apical), adjacent to either the mesial or distal surfaces of the interdental septum, during physiological drift of the rat molar teeth.…”
mentioning
confidence: 99%